Global-in-time solutions of 3-dimensional Vlasov-Poisson system - Parsa, Zohreh; Zadorozhny, V. (Вопросы атомной науки и техники, 2006)
In this paper, we consider 3-dimensional Vlasov-Poisson system and study their qualitative properties of globalin-time
solutions from the point of view integrability, stability, and optimality using the concept of special constructed
integral equations and the Lyapunov direct method. We provide criteria that guarantee the existence of solution
for the above mentioned properties By using this approach we reduce the problem of the charged-particle beam
transport, in particular, focusing with acceleration, to a problem of optimal control of dynamic system. В этой работе мы рассматриваем 3-х мерную систему уравнений Власова-Пуассона и изучаем качественные свойства их глобальных во времени решений с точки зрения интегрируемости, устойчивости и оптимальности использования концепции специально сконструированных интегральных уравнений и прямого метода Ляпунова. Мы приводим критерии, которые гарантируют существование решения для вышеупомянутых свойств. Благодаря использованию этого подхода мы свели проблему транспорта пучка заряженных частиц, в частности, фокусировку с ускорением к задаче оптимального управления динамической системой. В цій роботі ми розглядаємо 3-и вимірну систему рівнянь Власова-Пуассона та вивчаємо якісні
властивості їх глобальних за часом розв’язків з точки зору інтегрованості, стійкості і оптимальності
використання концепції спеціально сконструйованих інтегральних рівнянь та прямого методу Ляпунова. Ми
приводимо критерії, котрі гарантують існування розв’язків для вищезазначених властивостей. Завдяки
застосуванню цього підходу ми звели проблему транспорту пучка заряджених частинок, зокрема,
фокусування з прискоренням до задачі оптимального керування динамічною системою.